(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Oral spontaneity, a fundamental aspect of human communication, involves the ability to express oneself clearly, without extensive premeditation. Fixed expressions, also known as formulaic language, play a crucial role in enhancing the fluency and spontaneity of spoken language. These expressions, often consisting of idioms, proverbs, collocations, and other formulaic phrases, provide speakers with ready-made units that facilitate smooth interaction and reduce cognitive load during conversation. This paper explores the importance of fixed expressions in oral spontaneity and examines their role in enhancing communication in everyday conversations.